A 3D porous Ni-CeO2 nanosheet array as a highly efficient electrocatalyst toward alkaline hydrogen evolution. Issue 36 (28th August 2018) - Sun, Zhaomei; Zhang, Jiayu; Xie, Junfeng; Wang, Min; Zheng, Xiangjiang; Zhang, Zhen; Li, Xuemei; Tang, Bo
Abstract : A 3D porous Ni-CeO2 nanosheet array supported on a Ti mesh (Ni-CeO2 /TM) behaves as an efficient and stable alkaline HER electrocatalyst, offering a current density of 10 mA cm −2 at an overpotential of 67 mV. Abstract : In this Communication, we report a 3D porous Ni-CeO2 nanosheet array supported on a Ti mesh (Ni-CeO2 /TM) as an excellent electrocatalyst toward the alkaline hydrogen evolution reaction. To afford a current density of 10 mA cm −2, Ni-CeO2 /TM requires an overpotential as low as 67 mV, 77 mV lower than that of Ni/TM. Furthermore, the electrocatalyst shows good electrochemical durability with nearly 100% faradaic efficiency.